Evaluating Clinical Outcomes and Physiological Perspectives in Studies Investigating Respiratory Support for Babies Born at Term With or at Risk of Transient Tachypnea: A Narrative Review - McGillick, Erin V.; te Pas, Arjan B.; van den Akker, Thomas; Keus, J. M. H.; Thio, Marta; Hooper, Stuart B. (Frontiers in Pediatrics, 2022)
Respiratory distress in the first few hours of life is a growing disease burden in otherwise healthy babies born at term (>37 weeks gestation). Babies born by cesarean section without labour (i.e. elective cesarean section) are at greater risk of developing respiratory distress due to elevated airway liquid volumes at birth. These babies are commonly diagnosed with transient tachypnea of the newborn (TTN) and historically treatments have mostly focused on enhancing airway liquid clearance pharmacologically or restricting fluid intake with limited success. Alternatively, a number of clinical studies have investigated the potential benefits of respiratory support in newborns with or at risk of TTN, but there is considerable heterogeneity in study designs and outcome measures. A literature search identified 8 clinical studies investigating use of respiratory support on outcomes related to TTN in babies born at term. Study demographics including gestational age, mode of birth, antenatal corticosteroid exposure, TTN diagnosis, timing of intervention (prophylactic/interventional), respiratory support (type/interface/device/pressure) and study outcomes were compared. This narrative review provides an overview of factors within and between studies assessing respiratory support for preventing and/or treating TTN. In addition, we discuss the physiological understanding of how respiratory support aids lung function in newborns with elevated airway liquid volumes at birth. However, many questions remain regarding the timing of onset, pressure delivered, device/interface used and duration and weaning of support. Future studies are required to address these gaps in knowledge to provide evidenced based recommendations for management of newborns with or at risk of TTN.